The Effect of Visual, Audiotory, and Kinesthetic (VAK) Learning Models on Science Learning Outcomes - Eka Margareta Sinaga; Fahrur Rozi; Eka Kartika Silalahi; Erdiana Gultom; Betty Agatha Sihombing (Postgraduate, University of Mataram, 2025)
Low learning outcomes in IPAS (Natural and Social Sciences) among elementary school students are often caused by limited student engagement and learning methods that do not accommodate diverse learning styles. This study aims to determine the effect of the VAK (Visual, Auditory, Kinesthetic) learning model on the learning outcomes of fourth-grade students in IPAS subjects at SD Negeri 067246 Medan Tuntungan. The research employed a quantitative approach with a one-group pretest-posttest design, involving 30 purposively selected students from class IVB. Instruments used were learning outcome tests and student response questionnaires. The test assessed students’ knowledge before and after the implementation of the VAK model, while the questionnaire gathered students' responses toward the applied learning model. Data were analyzed using a paired sample t-test with SPSS version 22. Results showed an increase in the average score from 56.27 (pretest) to 85.33 (posttest). The t-test yielded a significant value of 0.000 < 0.05, indicating a statistically significant improvement in learning outcomes after the use of the VAK model. Furthermore, 60% of students responded positively to the learning process. These results suggest that the VAK model supports student engagement and accommodates various learning styles in IPAS learning.